Nutritional risk assessment and nutritional support in children with congenital diabetes during surgery - Lian Jiaoyan; Zhang Fang; Chen Haoyu (Open Medicine, 2025)
This work investigated intraoperative nutritional risk and nutritional support for children with congenital diabetes.